2017
DOI: 10.1002/jcph.895
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Lower Gastrointestinal Conditions: A Retrospective Cohort Study

Abstract: Several studies have reported constipation, abdominal pain, or diarrhea as common adverse events for statins. Statins are among the most commonly prescribed medications, and the impact on the prevalence of these conditions was rarely studied as main outcomes. The aim of this study is to determine if statin therapy is associated with constipation, abdominal pain, diarrhea, or colitis. This was a retrospective cohort study using a regional military health care data from October 1, 2003, to March 1, 2012. A prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Based on our inclusion/exclusion criteria, through full-text screening, we identified 61 studies for inclusion. 1 , 3 , 6 – 8 , 11 , 13 – 15 , 21 , 22 , 24 31 , 34 41 , 44 46 , 49 61 , 63 67 , 69 – 73 , 75 , 78 80 , 82 84 , 87 We included no additional studies through reference search and 4 additional studies solicited from coauthors that were not otherwise included, 19 , 23 , 43 , 81 resulting in a total sample of 65 studies, all of which were published in the English language; hence, no studies were excluded based on language.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our inclusion/exclusion criteria, through full-text screening, we identified 61 studies for inclusion. 1 , 3 , 6 – 8 , 11 , 13 – 15 , 21 , 22 , 24 31 , 34 41 , 44 46 , 49 61 , 63 67 , 69 – 73 , 75 , 78 80 , 82 84 , 87 We included no additional studies through reference search and 4 additional studies solicited from coauthors that were not otherwise included, 19 , 23 , 43 , 81 resulting in a total sample of 65 studies, all of which were published in the English language; hence, no studies were excluded based on language.…”
Section: Resultsmentioning
confidence: 99%
“…A list of all extraction items with summary statistics can be found in Table 1 . The studies identified were remarkably similar: 49 of 65 reported on surgical interventions; of the remaining16; 3 studied alternative treatments 8 , 25 , 29 ; 4 studied epidemiological risk factors like obesity, 22 old age, 21 opioid abuse, 23 and smoking 43 , 59 ; only 4 studies investigated pharmacological interventions 28 , 67 , 71 , 81 ; the remaining studied patient–professional–interaction or behavioural medicine, 19 , 66 radiotherapy, 49 implants, 69 or compared 2 disease progressions under routine care. 26 Of the 49 studies on surgical interventions, 23 focussed on postsurgical pain, with 3 investigating chronic postsurgical pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicated that statins tended to increase the risk of gastrointestinal discomfort or hemorrhage than other chronic medication users (93)(94)(95). Conversely, some studies did not show significant associations (96). The inconsistencies may result from varieties symptoms and severities of gastrointestinal discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a propensity score-matched cohort study of 12,684 patients found that regular statin users had a lower prevalence of diarrhea and colitis, and statin use was associated with a decreased risk of diarrhea (Pearlman et al, 2017;Suchartlikitwong et al, 2018). In a randomized controlled phase 2a trial, a proprietary modified-release formulation of lovastatin lactone lowered breath methane levels and improved stool frequency in patients with IBS-C (Gottlieb et al, 2016), which further suggested the potential protective effects of statins on IBS development.…”
Section: Figurementioning
confidence: 99%